A new species of the genus Utivarachna Kishida, 1940 (Araneae: Trachelidae) from China, with the first description of the male of U. fabaria Zhao & Peng, 2014 and a redescription of U. gui (Zhu, Song & Kim, 1998) - Jin, Chi; Yin, Xiangchu; Zhang, Feng (Zootaxa, 2015)
A new species belonging to the kinabaluensis group of the trachelid genus Utivarachna Kishida, 1940, U. lata sp. nov., is described from China. The male of U. fabaria Zhao & Peng, 2014 is described here for the first time based on specimens collected from Yunnan Province, China. The type material of U. gui (Zhu, Song & Kim, 1998) is re-examined and the species is redescribed.